Preparation of silver nanoparticles by pulsed laser ablation in liquid medium (International Journal of Engineering and Computer Science, 2014)
In present work Silver nonoparaticles have been prepared by using pulsed laser ablation ( Q -switched Nd:YAG) 1064nm  pluse duration and(E= 100mJ to 400mJ  ) of pure Ag mateal plate immersed in distilled water and dionized water  .The synthesized nanoparticles are characterized using transmittance electron microscopy (TEM) and UV-VIS spectrophotometer . The effect of the pulses energies and number. of shots have been reported .The silver nanoparticles exhibited asurface Plasmon resonance effect with wave length (λspr=400nm).The production of pure and spherical Ag with average size of (1-15nm) .All the size measurements have been confirmed by TEM.